Persistence of magnetic order in a highly excited Cu2+ state in CuO - Staub, U; de Souza, R; Beaud, P; Moehr-Vorobeva, E; Ingold, G; Caviezel, A; Scagnoli, V; Delley, B; Turner, J; Krupin, O; Lee, W; Chuang, Y; et al. (American Physical Society, 2014)
We use ultrafast resonant x-ray diffraction to study the magnetic order in CuO under conditions of high electronic excitation. By measuring changes in the spectral shape of the Cu2+ magnetic (1/2 0 â1/2) reflection we investigate how an intense optical pump pulse perturbs the electronic and magnetic states. We observe an energy shift in the magnetic resonance at short times after the pump pulse. This shift is compared with expectations from band structure calculations at different electronic temperatures. This spectral line shift indicates that although the electrons are heated to effective electron temperatures far above TN on a time scale faster than the experimental resolution, magnetic order persists in this highly excited state for several hundred femtoseconds. © 2014 American Physical Society.